University teachers data literacy for pedagogical decision making - Batuchina, Aleksandra; Melnikova, Julija (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The article has specifically sought to discuss university teachers’ data literacy skills that are important for the effective use of learning analytics in the teaching-learning process. Therefore, based on this analysis, teachers must achieve a certain level of data literacy to perform certain pedagogical actions. The main question of the current research is what data literacy skills teachers need to use learning analytics tools and make data-based pedagogical decisions. The article is based on the method of systemic literature analysis. The selected and analysed research papers allow us to present big data in education, highlight the pedagogical value of learning analytics technologies, and provide an overview of learning analytic tools. The results of the theoretical study showed that to use learning analytics tools, it is important for teachers to have skills such as digital literacy, data collection, data analysis and interpretation, etc.